The Polemic of Pig Kidney Xenotransplantation for Human Life Sustainability: (UINSI Samarinda, 2022)
End-stage renal disease (ESRD) cases continue to increase. However, the increase in cases of ESRD is not matched by the supply of kidneys as a condition for being able to perform a kidney transplant. Although this is not the only way to treat this case, it is only with a kidney transplant that the patient can truly recover. New York University Langone's success in xenotransplantation procedure using a genetically engineered pig kidney has become a new polemic in Islamic law issues. According to Islamic law, a pig has forbidden legal status (haram). This article analyzes the practice of xenotransplantation of pig kidneys in the human body using the concept of “Halal-haram” by Yusuf al-Qaradawi and “Maslahah” by Harun Sencal & Mehmet Asutay. This study is a qualitative method using a library research approach. This study found that it is permissible to do prohibited things during an emergency (daruriyat). In addition, in the realm of maslahah, hajiyat cannot beat daruriyat. Finally, summing up from these two Islamic scholars’ thoughts indicates that pig kidney xenotransplantation is prohibited as long as other alternatives to treat ERSD patients are available. Some options might be taken, such as hemodialysis and blood filtration (CAPD); therefore, it cannot be considered an emergency. Keywords: Pig kidney xenotransplantation, Islamic legal thoughts, halal-haram concept, principle of mashlahah